2017
DOI: 10.1177/1066896917724889
|View full text |Cite
|
Sign up to set email alerts
|

Warthin Tumor–Like Mucoepidermoid Carcinoma

Abstract: Mucoepidermoid carcinoma (MEC) shows a wide morphologic spectrum, including epithelium with oncocytic or squamous metaplastic changes overlying a prominent cystic architecture, as well as tumor-associated lymphoid tissue. We illustrate a case of MEC of the parotid in a 17-year-old female, in which all these features occurred extensively, such that they accounted for almost the entire neoplasm, and closely mimicked Warthin tumor histologically. This highlights the need for diagnostic awareness of this particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 3 publications
2
32
0
Order By: Relevance
“…In 2015, Ishibashi et al2 gave the first description of a Warthin-like variant of MEC. A similar histomorphology was also described by Heatley et al11 in a 17-year-old female presenting with a cystic lesion, which, on initial excision, resembled WT and classical mucoepidermoid morphology in the recurrent tumor. A retrospective review of the initial histology revealed the squamoid appearance and focal presence of mucin, which raised the suspicion of Warthin-like MEC.…”
Section: Discussionsupporting
confidence: 79%
“…In 2015, Ishibashi et al2 gave the first description of a Warthin-like variant of MEC. A similar histomorphology was also described by Heatley et al11 in a 17-year-old female presenting with a cystic lesion, which, on initial excision, resembled WT and classical mucoepidermoid morphology in the recurrent tumor. A retrospective review of the initial histology revealed the squamoid appearance and focal presence of mucin, which raised the suspicion of Warthin-like MEC.…”
Section: Discussionsupporting
confidence: 79%
“…Perplexingly, mucoid metaplasia may occur as well, which may easily lead to misdiagnosis of MEC [3]. However, metaplastic changes in WT are usually focal and admixed with necrosis, haemorrhages and fibrosis associated with prior biopsy [11]. On the other hand, Heatley et al described a case of Warthin-like MEC recurring after 4 years as obvious MEC [11].…”
Section: Discussionmentioning
confidence: 99%
“…However, metaplastic changes in WT are usually focal and admixed with necrosis, haemorrhages and fibrosis associated with prior biopsy [11]. On the other hand, Heatley et al described a case of Warthin-like MEC recurring after 4 years as obvious MEC [11]. Detailed evaluation of primary slides revealed a 1-mm distinctive area composed of small cysts lined by attenuated epithelial cells and mucous cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations